2020
DOI: 10.1504/ijicbm.2020.105560
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile apps in online shopping: scale development and validation

Abstract: The research paper focuses on the development of two scales to measure the applicability of the technology acceptance model and shopping motives behind the use of mobile shopping apps. Qualitative and quantitative techniques were employed to develop and validate the scales. An item pool was generated using a review of previous literature, in-depth interviews with online shoppers and experts from the retail industry. Based on quantitative analysis, two scales for mobile technology acceptance and motivation towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(127 reference statements)
0
5
1
Order By: Relevance
“…This signifies that users who perceive using FDAs as effortless are highly likely to consider such delivery applications as useful and continue to use them in the future as well. This result is contrary to study conducted by Khare and Sarkar (2020) and Yuan et al (2016), who concluded that PEOU does not have a significant influence on CI. Moreover, the study suggests that PU has a favourable influence on SAT and CI to use FDAs.…”
Section: Discussioncontrasting
confidence: 99%
“…This signifies that users who perceive using FDAs as effortless are highly likely to consider such delivery applications as useful and continue to use them in the future as well. This result is contrary to study conducted by Khare and Sarkar (2020) and Yuan et al (2016), who concluded that PEOU does not have a significant influence on CI. Moreover, the study suggests that PU has a favourable influence on SAT and CI to use FDAs.…”
Section: Discussioncontrasting
confidence: 99%
“…With recent technological developments, mobile technologies have established a special place in the minds of individuals (Esmaeilzadeh, 2021;Ma and McGroarty, 2017). Individuals are highly engaged in utilizing these technologies under various domains like m-Learning (Chao, 2019) mobile payments (Yan et al, 2021;Humbani and Wiese, 2019) mobile money (Dong et al, 2020) online shopping (Khare and Sarkar, 2020) and financial services (Museba et al, 2021). The aspect of Internet and social media has also enhanced the information acquisition process for retail investors on social media platforms by using mobile apps (Shiva and Singh, 2020;Wibisono and Ang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021; Humbani and Wiese, 2019) mobile money (Dong et al. , 2020) online shopping (Khare and Sarkar, 2020) and financial services (Museba et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Driediger and Bhatiasevi, 2019;Liu et al, 2020;Maduku and Thusi, 2023), decoupling different attributes of websites and their differential impacts on web-based retail shopping experience is required, as customers' utilitarian and hedonic expectations may vary in online shopping context (Liu et al, 2020). Indeed, the distinction between utilitarian and hedonic benefits, along with their impact on consumers' decision processes in the interactive e-environment, is considered to be one of the major factors explaining differences in consumer behaviour (Khare and Sarkar, 2020).…”
Section: Introductionmentioning
confidence: 99%